2018
DOI: 10.3390/microorganisms6020044
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Helicobacter pylori to Human Gastric Mucins Correlates with Binding of TFF1

Abstract: Helicobacter pylori binds to the gastric mucin, MUC5AC, and to trefoil factor, TFF1, which has been shown to interact with gastric mucin. We examined the interactions of TFF1 and H. pylori with purified gastrointestinal mucins from different animal species and from humans printed on a microarray platform to investigate whether TFF1 may play a role in locating H. pylori in gastric mucus. TFF1 bound almost exclusively to human gastric mucins and did not interact with human colonic mucins. There was a strong corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Thus, TFF1 seems to interact with the same mucin as TFF2 [43]. These results are in line with a study indicating that binding of TFF1 correlates with binding of H. pylori to gastric mucins recognized by the lectin GSA-II [78], i.e., MUC6 [43]. However, binding of TFF1 to MUC6 is in contrast to previous reports describing interactions with MUC5AC [79,80].…”
Section: Little Tff1 Binds To Mucin Muc6supporting
confidence: 89%
“…Thus, TFF1 seems to interact with the same mucin as TFF2 [43]. These results are in line with a study indicating that binding of TFF1 correlates with binding of H. pylori to gastric mucins recognized by the lectin GSA-II [78], i.e., MUC6 [43]. However, binding of TFF1 to MUC6 is in contrast to previous reports describing interactions with MUC5AC [79,80].…”
Section: Little Tff1 Binds To Mucin Muc6supporting
confidence: 89%
“…Comparison of the interactions of TFF1 and H. pylori with purified samples of animal and human mucins [65] detected a remarkable association between the affinities of TFF1 and H. pylori for different gastric mucin preparations (Spearman’s rho = 0.81; p = 0.002). Characterisation of the accessible saccharide lectin affinities in the mucin preparations favoured by TFF1 indicated that there was a preferential interaction with terminal non-reducing α- or β-linked N-acetyl-d-glucosamine or α-(2,3)-linked sialic acid or Gal-3-SO 4 2− .…”
Section: The Interaction Of H Pylori With Tff1 Is Mediated Via Glmentioning
confidence: 99%
“…1b) 21 . A lectin-like activity has also been reported for TFF1, which binds Helicobacter pylori lipopolysaccharide (LPS) in an α-glucosidase-sensitive manner 22 , and gastric mucin 23 . While unique protein-protein interactions may occur between the TFFs and their many reported binding partners 24 , a TFF lectin activity would also explain their association with such a diverse array of glycoproteins.…”
mentioning
confidence: 93%